Reconciling grain growth and shear-coupled grain boundary migration - Spencer L. Thomas (Nature Portfolio, 2017)
Conventional grain growth models assume the velocity of a grain boundary is proportional to its curvature but cannot account for the many deviations observed experimentally. Here, the authors present a model that connects grain growth directly to the disconnection mechanism of grain boundary migration and can account for these deviations.